Approaches to the diagnosis of Cutaneous Diseases Among Swimmers: Causes, Symptoms, Prevention, Treatment - Łazicka, Patrycja; Jakubowska, Eliza; Tarnowska, Julia (Quality in Sport, 2025)
Introduction The environment in which the sports enthusiast participates may influence the dermatoses that develop. Skin dermatoses are a significant health problem among athletes, especially swimmers, exposed to long-term contact with water and chemicals used in swimming pools. The use of appropriate diagnostic and preventive strategies, such as functional sports clothing, prevention before the occurrence or rapid diagnosis, can significantly reduce the risk of these diseases. Aim The aim of this article is to discuss the main approaches to the diagnosis of dermatoses in swimmers, their prevention and treatment. Materials and methods The review was based on the analysis of materials collected in the Google Scholar and, PubMed’’. The following keywords were entered during the search for scholarly articles: dermatoses, swimmers, skin infections, xerosis, sport. A total of 48 articles were considered for the study and verified for their relevance to the topic. State of knowledge Dermatoses in swimmers are the result of a combination of several factors, including impaired skin barrier, bacterial, viral and fungal infections, contact dermatitis, sun-related conditions or acne mechanica. Chemical agents such as chlorine used to disinfect swimming pool water may irritate the skin, causing contact dermatitis. Moreover, mechanical factors, such as skin friction against swimming equipment, and a humid environment leads to fungal and bacterial infections, combined with contact with allergens, e.g. latex, may lead to irritation, hives or other allergic reactions. Summary (Conclusions) Swimmers require a comprehensive approach that combines precise diagnostics with effective preventive measures. Proper skin care is crucial, including the use of emollients, protective creams and quick removal of chlorine residues from the body surface after training.